Arnold tongue entrainment reveals dynamical principles of the embryonic segmentation clock - Layague Sanchez, Paul Gerald; Mochulska, Victoria; Mauffette Denis, Christian; Mönke, Gregor; Tomita, Takehito; Tsuchida-Straeten, Nobuko; Petersen, Yvonne; Sonnen, Katharina; François, Paul; Aulehla, Alexander (eLife, 2022)
Living systems exhibit an unmatched complexity, due to countless, entangled interactions across scales. Here, we aim to understand a complex system, that is, segmentation timing in mouse embryos, without a reference to these detailed interactions. To this end, we develop a coarse-grained approach, in which theory guides the experimental identification of the segmentation clock entrainment responses. We demonstrate period- and phase-locking of the segmentation clock across a wide range of entrainment parameters, including higher-order coupling. These quantifications allow to derive the phase response curve (PRC) and Arnold tongues of the segmentation clock, revealing its essential dynamical properties. Our results indicate that the somite segmentation clock has characteristics reminiscent of a highly non-linear oscillator close to an infinite period bifurcation and suggests the presence of long-term feedbacks. Combined, this coarse-grained theoretical-experimental approach reveals how we can derive simple, essential features of a highly complex dynamical system, providing precise experimental control over the pace and rhythm of the somite segmentation clock.